PERTANGGUNGJAWABAN OKNUM NOTARIS DALAM TINDAK PIDANA TURUT SERTA MELAKUKAN PENGGELAPAN SERTIFIKAT - Dicky Armandau (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACTA Notary is an ordinary person who in carrying out his duties may deviate from the applicable legal rules.The method used in this research is normative, which examines and relates criminal acts committed by a notary with the concept of legal principles and elements of criminal acts based on the Criminal Code (KUHP) and the Law on Notary Positions (UUJN).The purpose of this study is to find out how the responsibility of notaries in criminal acts of participating in embezzlement of Property Rights Certificates based on Court Decisions and how the legal consequences of criminal convictions participate in embezzling Property Rights Certificates by notaries who have permanent legal force against the implementation of the position of a Notary and Notary code of ethics.The result of this research is that although the Notary Position Act (UUJN) does not regulate the existence of criminal sanctions against a Notary, it does not mean that a Notary as a public official is immune from the law. If a Notary in carrying out his duties is proven to have committed a crime and fulfills its elements, a Notary can be sentenced to criminal sanctions in accordance with the crime he has committed, which will refer to the Criminal Code (KUHP).Criminal responsibility for embezzlement committed by a Notary, namely a Notary will be given a prison sentence if he has fulfilled the elements of a criminal act of embezzlement as stipulated in Article 372 of the Criminal Code in conjunction with Article 55 paragraph (1) first.The legal consequences received by a Notary if he commits a criminal act and has permanent legal force with imprisonment for less than 5 (five) years, the Notary can still continue his profession as a Notary as long as he is not dishonorably dismissed by the Ministry of Law and Human Rights. Keywords: Accountability; embezzlement; Notary